Combined Use of Broad-Spectrum Antibiotics in Phthisiology - D. S. Vailenko; T. P. Tananakina; Yu. G. Pustovoy; V. V. Baranova; V. I. Shmatkov; A. R. Zanin (Фундаментальная и клиническая медицина)
Aim. To investigate pharmacokinetic and pharmacodynamic interactions of levofloxacin, kanamycin and linezolid in combined chemotherapy of multidrug-resistant tuberculosis.Materials and Methods. We investigated pharmacological interactions between levofloxacin, kanamycin and linezolid using GalaxyWEB GalaxySagittarius – AlphaFold software.Results. We found that levofloxacin can interact through the carboxyl group (–COOH) with compounds containing an amino group, in particular with linezolid and kanamycin, in order to form a carbamide bond -CO-NH-. Levofloxacin is also able to form an azomethine bond via the carbonyl group –C = O with drugs containing the primary amino group (kanamycin and linezolid). 3D models of the drug compounds with plasma proteins were visualized and protein matches of paired intake of drugs were determined: Levofloxacin – Linezolid pair – 181 matches, Levofloxacin – Kanamycin pair – 11 matches, Kanamycin – Linezolid pair – 8 matches. After 1.5-2 hours after the intake of levofloxacin – linezolid - kanamycin, these drugs reached peak concentrations. Levofloxacin and linezolid were primarily metabolized in the liver and kanamycin has not been metabolized at all. All three drugs were excreted by the kidneys.Conclusion. The analysis demonstrated effectiveness of Galaxy Sagittarius – AlphaFold technology and found a significant level of drug-protein complexes. The interaction of linezolid, levofloxacin and kanamycin led to an increase in the effectiveness and safety of pharmacotherapy, underlying their rational combination.